Microsatellite instability and Beta2-Microglobulin mutations as prognostic markers in colon cancer: results of the FOGT-4 trial - Schulz, Anna; Knebel Doeberitz, Magnus von; Kloor, Matthias (British journal of cancer, 2012)
Background: High-level microsatellite instability (MSI-H) has been reported as a prognostic marker in colon cancer. We here analysed the prognostic significance of MSI and mutations of the Beta2-Microglobulin (B2M) gene, which occur in about 30% of MSI-H colon cancer, in the cohort of the prospective FOGT-4 (Forschungsruppe Onkologie Gastrointestinale Tumoren, FOGT) trial. Methods: Microsatellite instability status was determined using standard protocols (NCI/ICG-HNPCC panel and CAT25) in 223 colon cancer lesions. Beta2-Microglobulin mutation status was evaluated by exon-wise sequencing in all MSI-H lesions. Results: Patients with MSI-H (n=34) colon cancer presented with a significantly lower risk of relapse after 12 months of follow-up compared with MSS (n=189) colon cancer patients (5 year time to relapse: MSI-H 0.82 vs MSS 0.66, P=0.03). No significant difference in overall survival was detected. Beta2-Microglobulin mutations were identified in 10 (29.4%) out of 34 MSI-H colon cancers and were associated with a complete absence of disease relapse or tumour-related death events (P=0.09). Conclusion: The risk of late disease relapse was significantly lower in patients with MSI-H compared with MSS colon cancer. Moreover, B2M mutations may contribute to the favourable outcome of MSI-H colon cancer patients and should therefore be evaluated as a potential prognostic marker in future clinical trials.